Assembly of pigeon circovirus-like particles using baculovirus expression system. (February 2020) - Gai, Weiwei; Zheng, Wenwen; Zhao, Zhongxin; Wong, Gary; Sun, Peilu; Yan, Lina; He, Hongbin; Zheng, Xuexing
Abstract: Pigeon circovirus (PiCV) is able to infect racing and meat pigeons of all ages and is a key factor that triggers young pigeon disease syndrome (YPDS). PiCV vaccine research has been impeded because PiCV cannot be grown or propagated in cell cultures. Virus-like particles (VLPs), which can be generated by a wide range of expression systems, have been shown to have outstanding immunogenicity and constitute promising vaccines against a wide range of pathogens. Cap protein, which contains neutralizing antibody epitopes, is the only capsid protein of PiCV. In this study, the baculovirus expression system was utilized to express the PiCV Cap protein, which was self-assembled into VLPs with a spherical morphology and diameters of 15–18 n m. Specific antibodies against the Cap protein were induced after BALB/c mice immunized intramuscularly (i.m.) with VLPs combined with adjuvant. Based on these findings, PiCV VLPs may be a promising candidate vaccine against PiCV. Highlights: PiCV VLPs were assembled by Cap protein expressed in insect cells. PiCV VLPs resemble native viruses but lack infectious genetic material. PiCV VLPs induced high Cap-specific antibody titers in immunized mice. PiCV VLPs is a promising vaccine candidate due to strong immunogenicity and safety.